Computing Platforms for Software-Defined Radio - Hussain, Waqar; Nurmi, Jari; Isoaho, Jouni; Garzia, Fabio (Springer International Publishing : Imprint: Springer, 2017)
This book addresses Software-Defined Radio (SDR) baseband processing from the computer architecture point of view, providing a detailed exploration of different computing platforms by classifying different approaches, highlighting the common features related to SDR requirements and by showing pros and cons of the proposed solutions. Coverage includes architectures exploiting parallelism by extending single-processor environment (such as VLIW, SIMD, TTA approaches), multi-core platforms distributing the computation to either a homogeneous array or a set of specialized heterogeneous processors, and architectures exploiting fine-grained, coarse-grained, or hybrid reconfigurability. Describes a computer engineering approach to SDR baseband processing hardware; Discusses implementation of numerous compute-intensive signal processing algorithms on single and multicore platforms; Enables deep understanding of optimization techniques related to power and energy consumption of multicore platforms using several basic and high-level performance indicators; Includes prototyping details of single and multicore platforms on ASICs and FPGAs.